Consolidation immunotherapy following concurrent chemoradiotherapy in a patient with sinonasal NUT carcinoma: a case report - Geng, Xiaotao; Chang, Xiaolong; Wang, Xiaoli; Li, Shunjia; Han, Guiyan; Song, Zhiyu; Hao, Furong; Li, Jianwen (Frontiers in Oncology, 2024)
BackgroundNuclear protein in testis (NUT) cancers, also known as midline cancers, tends to occur in organs near the midline, such as the nasal sinuses and mediastinum. NUT carcinoma is very rare and has a poor prognosis.Case descriptionWe report the case of a 44-year-old female patient with sinonasal NUT carcinoma who presented with a soft tissue mass in the left frontal sinus, ethmoid sinus, and left nasal cavity on computed tomography; the tumor was poorly demarcated from the left rectus medialis. After discussion with a multidisciplinary team with expertise on head and neck tumors, the patient was considered inoperable, and definitive concurrent chemoradiotherapy (CCRT) was recommended. The patient underwent CCRT followed by three cycles of consolidation chemotherapy with albumin-bound paclitaxel and nedaplatin. Subsequently, the patient underwent 16 cycles of consolidation therapy with the programmed death–1 (PD-1) inhibitor tislelizumab. The immune-related adverse events included grade 2 hypothyroidism. After CCRT, consolidation chemotherapy, and consolidation immunotherapy, the patient achieved a favorable outcome. The patient survived for 31 months, and there were no signs of recurrence or metastasis during follow-up.ConclusionAt present, there is no clear consensus on the consolidation treatment plan after CCRT for sinonasal NUT cancer. We used consolidation immunotherapy for the first time and achieved good efficacy, providing an innovative and promising treatment plan for refractory sinonasal NUT cancer.